Upaya melatih kreativitas anak melalui media vegetable painting di PAUD Al-Fattah Kota Bengkulu - Wahyu Dwi Ramadhani (Journal Of Dehasen Educational Review, 2020)
This study aims to describe the efforts and obstracles in training children's creativity through vegetable painting in PAUD AL-FATTAH of Bengkulu City. This type of research is a qualitative descriptive study involving teachers in PAUD AL-FATTAH. Data were collected through interviews, documentation and data were analyzed qualitatively by using data reduction, display and verification methods. The results of this study indicate that learning by using vegetable painting in PAUD AL-FATTAH, Group B children get three star grades already starting well. Teachers of Group B PAUD AL-FATTAH preparE the learning process by using the online system because it was in a state of covid-19 pandemic. That is, children can still be creative according to their own creations. Meanwhile, children's creations in the form of green and white green vegetables produce images of flowers, roses, and a mixture of vegetables, cabbage, and oyong to produce a viewpoint. This is where the activity of vegetable painting helps children to practice their creativity.